ANALISA FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN PUBLIK TERHADAP TAMAN KOTA SEBAGAI RUANG PUBLIK DI KOTA SURABAYA - Trihastusti, Adiati; Santoso, Sigit; Soepriyadi, Nono (JEA17: Jurnal Ekonomi Akuntansi, 2019)
ABSTRACT The city of Surabaya as a metropolitan city is experiencing a rapid development revolution to meet heterogeneous public demand, which is certainly a concern for the city government. As a metropois city that is growing rapidly in economic development, of course it is also followed by a rapid population as well. The rapid development also still considers environmental aspects and the beauty of the city of Surabaya, so the government is expected to provide public space or Green Open Space (RTH) that can be utilized by the community. In Law No. 26 of 2007, the need for the provision and utilization of green open space with a proportion of the area set at least 30 percent of the total area of the city. RTH is utilized as a public space and by Surabaya Mayor B Risma is built a public facility in the form of a city park, which is an active park and its facilities in the city of Surabaya. RTH service efforts are also being intensified by the Surabaya City Green and Open Space Agency at present. The number of vacant lots in the middle of the city is now used as city parks and urban forests, and there are dozens of city parks owned by Surabaya City. Therefore, it is necessary to conduct research to determine the impact, benefits, influence and satisfaction of the community towards this policy. From the results of the analysis and discussion it is known that the Sports Facilities, Wifi Area, Street Vendors, and Recreation Areas variables have a positive influence on people's satisfaction. Where the city park as a public space part of green space has a contribution of 89.5% to the satisfaction of the community, with the facilities contained in the city park. Therefore Surabaya Mayor B Risma's program builds public facilities in the form of city parks, namely active parks and their facilities in the Surabaya city area, which are very significant and beneficial to the public. Keywords: kepuasan publik, taman kota (Sarana Olahraga, Area Wifi, Pedagang Kaki Lima /Kuliner, Tempat Rekreasi), Ruang Publik.